Transplantasi Regulatory Impact Assessment+: Reposisi Naskah Akademik dalam Pembentukan Undang-Undang - Al Faruq, Muhammmad Hamzah; Era Ruhpinesthi, Garuda; Sekar Ismaya, Alfatania (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2024)
As far as the Law Number 13 of 2022 was issued, the Academic Draft making process still shows the minimum participation of affected communities. Neither the Law nor the Guidance of Academic Draft making process that was published by the House of Representatives Expertise Body have regulated consistent research method. This fact implies the quality of the current Academic Draft that has not yet accommodated Regulatory Impact Assessment methods such as determining alternative policy and impact analysis that would produce the best policy. This normative juridical research aimed to get a better understanding of: (i) The regulatory and practices problems of preparing Academic Draft related to the principle of transparency in the lawmaking and (ii) The mechanisms for repositioning Academic Draft related to the principle of transparency through the application of Regulatory Impact Assessment+. This research is normative legal research with secondary data. The results showed two things. First, in terms of regulation and practice, there is a problem that Academic Draft is still positioned as a justification for the Law and the reality of Academic Draft preparation related to the principle of transparency in the lawmaking is still weak based on the analysis of the role of the community in the dynamics of implementing research methods that are considered insignificant. Second, Academic Draft repositioning mechanism is needed through the application of Regulatory Impact Assessment+ with the following five things: i) repositioning the use of Regulatory Impact Assessment in the stages of lawmaking, ii) loading the inventory mechanism of affected communities, iii) containing detailed instructions for the implementation of Academic Draft preparation research carried out, iv) changing the Academic Draft structure through adjustments to Regulatory Impact Assessment+ to accommodate alternative policy mechanisms, to v) detailing procedures and aspects of consideration for implementing the Cost-benefit Analysis mechanism.